Effect of Instructional Approaches on Financial Accounting Achievement among Secondary School Students in Gombe State, Nigeria - Inuwa, Umar (Kashere Journal of Management Sciences, 2024)
The study examined the effects of instructional approaches on secondary school students’ achievement in financial accounting in Gombe state, Nigeria. A pre-test-post-test-control group design was adopted where 240 students from twelve randomly selected schools participated in the study. The Financial Accounting Achievement Test (FAAT) was used as an instrument for data collection. The data collected from the study were analyzed using analysis of variance (ANOVA) and analysis of covariance (ANCOVA). At the pre-test stage, the study found that there was no statistically significant difference in the achievement of students who were assigned to the experimental and control groups. However, at the post-test stage, the study has proved that the financial accounting achievement of students who were exposed to the cooperative approach was significantly better than that of their counterparts who were exposed to the guided discovery, demonstration and conventional approach. This suggested cooperative approach as the most effective approach to enhance the financial accounting achievement of the secondary school students.